Infestation of Rhyzopertha dominica first instars on different classes of wheat - Andrada, Mario (Kansas State University, 2017)
The lesser grain borer, Rhyzopertha dominica (F.), females lay eggs loosely outside of wheat kernels. Larvae hatching from eggs enter wheat kernels to complete immature development. Four laboratory experiments were conducted to understand the wheat kernel infestation by first instars of R. dominica at 28°C and 65% r.h. The first experiment compared different kernel to first instar ratios on sound hard red winter (HRW) wheat class, probability of successful infestation, and subsequent adult development as affected by site of feeding on the kernels. Infested kernels were dissected 21 d after infestation to determine stage of development and larval weight. Development of larvae to adulthood was monitored for 50 d from time of infestation. Different kernel to first instar ratios did not affect probability of infestation, entry site preferences, larval development and weight, and days to adult emergence. In the second experiment one first instar was placed with a kernel on each of seven different wheat classes. Wheat kernels were artificially-damaged with a microdrill at the germ, endosperm, and brush end, and the sound kernels served as the controls. At 21 d, 82-90% of artificially-damaged HRW wheat kernels were infested by larvae versus 12% for sound kernels. Five times fewer hard white (HW) wheat sound kernels were infested by larvae compared with infestation in soft white (SW) wheat kernels. Sound kernels of durum, soft red winter (SRW), hard red spring (HRS), and hard white spring (HWS) wheat classes were more resistant to larval infestation than artificially-damaged kernels. Majority of first instars preferred germ as the entry site on HRW, HWW, SRW, and HWS wheat classes. Germ entry promoted faster larval development, leading to heavier larvae, and higher kernel weight losses. Adult emergence was earlier by 3-7 d compared with other sites across all 6 wheat classes, except for SWW class, where adult emergence was nil at 50 d. In the third experiment, speed of larval development on artificially-drilled HRW wheat kernels on different kernel sites. Three-hundred kernels each were drilled near the germ, endosperm, and brush end, and one first instar was placed per kernel in a glass vial. Kernels from glass vials were dissected every 3 d for 30 d and larval head capsule was measured. Larval development was fastest on the germ, followed by endosperm, and brush end. In the fourth experiment short-term feeding by R. dominica adults on infestation by first instars on sound wheat kernels was determined. Two laboratory tests were conducted with single and grouped (10) kernels using either two adults or two first instars per kernel. Signs of feeding were monitored for 21 d in single kernels and 7 d in grouped kernels. There was a significant association between adult feeding and larval infestation responses in single and group kernel tests. In conclusion, understanding factors that contribute to first instar establishment in wheat kernels will have impacts in breeding varieties that could be resistant and designing grain-handling equipment to minimize grain damage to mitigate R. dominica infestation of wheat.
Keywords: Wheat; Lesser grain borer; First instars; Infestation; Development; Adult emergence